Work Life in Indian Philosophy - Mala Sharma (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
“Ethics” was once considered irrelevant by corporate loyalists, but now discussion of it is increasingly seen as not only important but also as critical to a company’s success. The paper is a theoretical review. The purpose and objective of the paper is to explore and understand the meaning of business ethics in the context of Indian philosophical thought. The study focuses mainly on the contribution of Hindu philosophical thought though makes reference to other philosophical thoughts namely Buddhism, Jainism and Arthashastra. Keywords: Indian philosophy and ethics, moral, ethics in business management.